Demographic Correlates of Hoarseness of Voice & their Etiological Factors - Dileep Kumar Khatri, Muhammad lqbal Rao, Noor Alam Ansari , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To determine the demographic correlates and their association with etiological factors for hoarseness ofvoice. Study Design: Cross sectional study. Place & Duration: Department of ENT, Muhammad Medical College, Mirpurkhas from 26th April 2013 to 25th October 2013. Material & Methods: Total 97 patients with complaint of hoarseness of voice for more than one week were included. Temperature was noted. Indirect laryngoscopy was carried out to see the state of laryngeal mucosa for redness, congestion, vocal nodules and growth. Chi square test was applied to see the association between variables. Results: The mean age of the patients was 41.7±1 1 .2 years with 50.5% patients having laryngeal infection, 35.1% having laryngeal tumor and 14.4% having vocal nodule. Most of the patients belonged to 31-50 years (62 patients), among them 38 had laryngeal infection, 5 had vocal nodule and 19 had tumor of larynx. Male patients were more for the complaint of hoarseness of voice (76 patients), among them 35 had laryngeal infection, 9 had vocal cord nodule and 32 had tumor of the larynx. The road side vendors were more in the study, among them, 10 had laryngeal infection, 4 vocal nodule and 18 had tumor of larynx. Conclusion: The etiology ranges from trivial infections to life threatening malignancy. Hoarseness should not be ignored if it persists for more than three weeks particularly in men, elderly and professionals prone to it. Key Words: Hoarseness, Laryngeal Infection, Laryngeal Tumor, Vocal Nodule